THER-17. BRAF-V600E DEGRADATION AS A THERAPEUTIC STRATEGY IN BRAF-V600E MUTANT GLIOMAS. (23rd April 2019) - Zhao, Guisheng; Muldoon, Daniel; Mo, Xiulei; Tang, Cong; Fu, Haian; Gustafson, W Clay; Weiss, William A; Nicolaides, Theodore
Abstract: INTRODUCTION: Oncogenic, driver BRAF-V600E mutations are frequently found in pediatric gliomas. While small molecule inhibitors of BRAF and/or MEK kinases are showing early clinical efficacy against these tumors, no experimental strategies thus far have focused on the degradation of the mutant BRAF protein itself. Members of our team have recently discovered that in contrast to wildtype BRAF protein, BRAF-V600E protein binds to aurora kinase A. We therefore hypothesized that CD532, a novel small molecule allosteric aurora kinase A inhibitor, would preferentially degrade BRAF-V600E over wildtype BRAF, and lead to decreased cell growth in BRAF-V600E gliomas. METHODS: We used an isogenic system of 3T3 fibroblasts transduced with empty vector, wildtype BRAF, KIAA1549:BRAF fusion, and BRAF-V600E, as well as established glioma cell lines AM38 (BRAF-V600E homozygous), DBTRG (BRAF-V600E heterozygous), U87 (BRAF wildtype), LN229 (BRAF wildtype with NF1 deficiency) and immortalized normal human astrocytes (NHA, BRAF wildtype). We performed cell cycle and viability assays, as well as immunoblot analyses for wildtype BRAF and BRAF-V600E. Cells were treated with CD532 at doses of 0.5 and 1 uM. RESULTS: The OncoPPi network mapping revealed that aurora kinase A binds to only BRAF-V600E but not wildtype BRAF protein. BRAF-V600E mutant cell lines showed a dramatic decrease in BRAF-V600E expression level after CD532 treatment. This was accompanied by a significant decrease in growth rate. Cells containing only wildtype BRAF or KIAA1549:BRAF did not show any changes in BRAF expression and had less inhibited growth after treatment with CD532. CONCLUSIONS: Degradation of BRAF-V600E mutant protein through inhibition of aurora kinase A shows preclinical efficacy against BRAF –V600e gliomas.